ANALISIS TIMBAL (Pb) DI SEKITAR PELABUHAN SOEKARNO HATTA MAKASSAR MENGGUNAKAN METODE KURVA KALIBRASI, ADISI STANDAR TUNGGAL DAN ADISI STANDAR BERGANDA - Bulkis Musa; Abdul Wahid Wahab; Adam Nur Ahmad; Adriani; Wildan Mubaraq (Jurnal Teknik SILITEK, 2024)
The analysis of lead heavy metal around the port of Soekarno Hatta Makassar has been carried out using the calibration curve method, single standard addition and double standard addition methods. The concentrations obtained were obtained using the calibration curve method for point 1 of 0.388 mg/L and for point 2 of 0.5725 mg/L, the single standard addition method for point 1 was 0.1116 mg/L and for point 2 was 0.1347 mg/L, and the double standard addition method for point 1 was 0.4278 mg/L and for point 2 was 0.5869 mg/L. The correlation coefficient of each method was in the range of 0.995 - 1. For LoD and LoQ analysis, the quantity limit and detection limit values for lead heavy metal analysis from AAS tools were 0.1778 mg/L and 0.5656 mg/L. The results of the precision test for the calibration curve method for point 1 were 9.462 % and for point 2 was 2.472 %, the single standard addition method for point 1 was 34.64 % and for point 2 was 24.59 %, and the double standard addition method for point 1 is 8.07% and for point 2 is 9.63%.